Taking it to the Street: Reclaiming Australia in the Top End. (4th May 2017) - Kelly, David; Lobo, Michele
ABSTRACT: Since Cronulla, racism and the resurgence of White ethno-nationalism is again contesting the diversity of Australian national imaginaries. This paper argues, however, that encounters with Aboriginality and connection to Country provide fresh perspectives that affirm difference. The paper focuses on Broome and Darwin, two urban centres in northern Australia with a visible Aboriginal population that have been the focus of little contemporary research on intercultural relations compared to southern cities. Such an optics from the Top End is necessary, given its unique histories of Aboriginal and ethnic minority contact that predate White settlement, as well as the ongoing resistance to dehumanising, interventionist and racially discriminatory practices and policies. This paper places affirmative 'events of commoning' at the core of emancipatory politics. Such a politics is informed by the theoretical conceptualisation of commoning as a relational process of 'being-in-common' that unfolds in cooperative practices and collective action. We focus on two events – a protest event in Broome as response to the closure of remote Aboriginal communities and a 'celebration walk' through the streets of Darwin during NAIDOC week. These 'noisy' and 'quiet' struggles reclaim the street and provide the possibility to think about how a common world can be recomposed through embodied potentiality.